Youth resistance and KGB activity in the 9th decade of XX century. - Žiūkas, Mindaugas (Genocidas ir rezistencija, 2003)
The KGB Vilnius City Division was particularly interested in ‘anti–social youth groups’, hippies, punks, and Krishna followers. The situation in youth meeting places – discotheques, clubs, cafés, as well as karate sections – was monitored. By 1985, the KGB Vilnius City unit managed to minimise the anti–Soviet activities of schoolchildren in Vilnius City. For this purpose, the security services not only used the agency and trusted persons at their disposal, but also the MVD organs with the Komsomol unit of F. Dzerzhinsky. The large number of operatives working under the ‘5th line’ showed that rebellious ideas were rife among the young people and that the KGB was unwilling to put up with the anti–Soviet activities of school students. In fact, these activities consisted only of writing and distributing hostile notes, letters, and leaflets with anti–Soviet content, and unrest during sports competitions.
Keywords: KGB; civil resistance; youth resistance; Vilnius; KGB methods